Assessment of negative appendectomy in acute appendicitis diagnoses - Francisco Antonio Rodriguez-Garcia; Carlos Enrique Rodríguez-Sánchez; Julio Cesar Naranjo-Chávez; Christian Jorge Torres-Ortiz-Ocampo; Fabián Rojas-Larios; Karen Covarrubias-Ramírez; Eduardo Missael Evangelista-Ruiz; Quitzia Libertad Torres-Salazar (Surgery in Practice and Science)
Background: A negative appendectomy is a surgery performed due to a clinical suspicion of acute appendicitis, but no evidence of inflammation is identified upon examination. The main reason is the incorrect diagnosis of acute appendicitis, which remains a challenge, especially in developing countries, where the rates are different among populations. This study aims to explore the prevalence of negative appendectomies in a regional hospital and evaluate the diagnostic methods used in clinical practice. Materials and methods: A retrospective analysis was conducted on patients who underwent emergency appendectomy between 2021 and 2022. Negative appendectomy was defined as the absence of histopathological evidence of acute appendicitis postoperatively. Results: Out of 324 patients, 38 were found to have undergone a negative appendectomy, representing a two-year rate of 11.7%. Imaging was performed in 78% of cases, but no significant difference was observed in its use between patients with positive and negative appendectomies. Differential diagnoses showed pathologies such as cysts and intestinal lesions. The Alvarado score was found to be a useful tool when applied with a threshold score of 7. However, variability in clinical presentations such as nausea/vomiting, anorexia, right iliac fossa tenderness and fever highlighted the limitations of relying solely on this metric. The factors associated with negative appendectomy were previous abdominal surgery, Alvarado score <7, abdominal pain, rebound tenderness, leukocytosis and neutrophilia. Conclusions: The prevalence of negative appendectomies at our institution was 11.7%. Despite the widespread use of diagnostic imaging and clinical scoring systems, improvements in diagnostic accuracy are necessary to reduce the rate of unnecessary surgeries.